2018
DOI: 10.1097/jom.0000000000001345
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Determinants of Workplace Violence Against Hospital Workers

Abstract: Objective To identify organizational factors contributing to workplace violence in hospitals. Methods A questionnaire survey was conducted in 2013 among employees in a Midwestern hospital system (n=446 respondents). Questions concerned employees’ experiences of violence at work in the previous year and perceptions of the organizational safety climate. Logistic regressions examined staff interaction and safety climate factors associated with verbal and physical violence, respectively. Results Interpersonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 46 publications
5
59
2
5
Order By: Relevance
“…Finally, experiencing workplace violence was another key variable associated with our primary outcomes. Workplace violence is associated with poor quality of life, increased staff turnover, BO and STS, and poor patient care outcomes in other studies (Arnetz et al ; Beck ; Itzhaki et al ; Lanctôt & Guay ). We found that both witnessing and experiencing workplace violence were significantly associated with poor CS and increased BO and STS scores.…”
Section: Discussionmentioning
confidence: 78%
“…Finally, experiencing workplace violence was another key variable associated with our primary outcomes. Workplace violence is associated with poor quality of life, increased staff turnover, BO and STS, and poor patient care outcomes in other studies (Arnetz et al ; Beck ; Itzhaki et al ; Lanctôt & Guay ). We found that both witnessing and experiencing workplace violence were significantly associated with poor CS and increased BO and STS scores.…”
Section: Discussionmentioning
confidence: 78%
“…Additionally, compared with other forms of violence, internal and psychological violence is more strongly associated with organizational factors (Arnetz, Hamblin, Sudan, & Arnetz, 2018;Kwan, Tuckey, & Dollard, 2016;Van De Griend & Messias, 2014;Zhang et al, 2017); therefore, the associations between workplace violence and health can be confounded by organizational psychosocial work conditions. Psychosocial work conditions were reported to be associated with many stress-related disorders (Nieuwenhuijsen, Bruinvels, & Frings-Dresen, 2010); however, these conditions have rarely been considered in previous studies analysing the relationship between workplace violence and health.…”
Section: Introductionmentioning
confidence: 99%
“…Interpersonal trust, a part of interpersonal relationships, should also associate with workplace violence. Besides, interpersonal conflict was an important factor associated with hospital workers which had been identified in previous studies [24]. As the association between and interpersonal conflict [25], we can also believe the effect of workplace violence on interpersonal trust.…”
Section: Introductionmentioning
confidence: 54%